PERANCANGAN SISTEM INFORMASI MARKETING BERBASIS WEBSITE PADA PERUSAHAAN DISTRIBUTOR PT. SBM - Hartono, Sugiarto (Infotech: Journal of Technology Information, 2020)
Today, the use of the internet among the public is increasing. This gives a fairly large number in the business world specifically commercial companies. The internet makes it easier for companies to carry out sales activities, for example in marketing, sales, customer relations, or supplier relations. The objectives of the study were approved and a web application was made that made it easy for PT. SBM and other companies to promote its products to the general public. General problems at PT. SBM is limited in funds and resources for approval of a product. Therefore, we need a website that can help introduce or promote products that will be sold to the general public regardless of distance and time, as well as saving promotional costs. Data collection methods used are through surveys, interviews, and literature studies. The application design method uses the Object Oriented Analysis Diagram (OOAD) method which is divided into 2 processes, namely analysis and design. The research results consist of a web that can promote company products or individuals that are more effective and efficient. The conclusion of this research is the production of web-based e-marketing that can support companies or individuals in supporting their products.